PENGARUH GAYA HIDUP, KELOMPOK REFERENSI DAN SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN DAN MINAT BELI ULANG DI COFFEE SHOP PADA GENERASI Z DI KOTA PEKANBARU - Refnaldo Refnaldo; musfar firli tengku; wasnury rendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The manifestation of today's lifestyle is hanging out in coffee shops,especially young people who are dominated by generation Z. There are manyreasons someone spends time in coffée shop, in addition to consuming food anddrinks as well as to show it off on social media among young people. Referencegroups are very important points in shaping the buying behavior of Generation Z.Social media also makes it easier for coffee shop businessmen to carry outmarketing and promotional activities. This study aims to determined influencelifestyle, reference groups, and social media marketing have on purchasingdecisions and intention to repurchase coffee shops by Generation Z in PekanbaruCity. Primary data were collected by using a questionnaire as a researchinstrument. The study used 100 people who was Generation Z in Pekanbaru City.Technique sampling was used non-probability sampling technique. The methodused was Explanatory Research with data analysis test, classical assumption test,hypothesis testing and path analysis as data testing. The results of this studyindicate that lifestyle variables, reference groups, and social media marketingpartially have a significant effect on purchasing decisions at coffee shops.Lifestyle variables, reference groups, and social media marketing have asignificant effect on repurchase intention through purchasing decisions at coffeeshops. The purchasing decision variable has a significant effect on buying interestin the coffee shop Keywords: Lifestyle, Reference Group, Social Media Marketing, Purchase Decision,Repurchase Interest, Generation Z.